Extracorporeal membrane oxygenation to support repeated whole-lung lavage in a patient with pulmonary alveolar proteinosis in life threatening dyspnoe – a case report. Issue 1 (December 2015) - Krecmerova, Martina; Mosna, Frantisek; Bicek, Vladimír; Petrik, Frantisek; Grandcourtova, Alzbeta; Lekes, Marek; Vymazal, Tomas
Abstract Backgroud Pulmonary alveolar proteinosis is a rare disorder that is characterized by a large accumulation of lipoproteinaceous material within the alveoli. This causes respiratory failure due to a restriction of gas exchange and changes in the ventilation/perfusion ratio. Clinical symptoms are variable and depend on the severity of damage of the lung parenchyma. Treatment method is whole-lung lavage, where the accumulated lipoproteinaceous material is removed using large quantities of saline. Case presentation This case report describes a 45 year old patient with advanced pulmonary alveolar proteinosis. Due to the presence of severe global respiratory insufficiency, this patient could not undergo the classic whole-lung lavage using a double-lumen tube and selective lung ventilation. The whole-lung lavage was performed with the support of veno-venous extracorporeal membrane oxygenation. A total of 27 l of warm saline was used. Conclusion According to the current published literature, whole-lung lavage with extra-corporeal membrane oxygenation support is a very rare treatment method. Even when taking into account all of the risks associated with whole-lung lavage and v-v extracorporeal membrane oxygenation support, we found that this technique is very effective and, without a doubt, it saved the life of our patient.